Dual-Working-Modes-Based Common Grounded Nonisolated DC-DC Converter With a Wide Voltage-Gain Range for Photovoltaic Applications - Li, Zou; Liu, Junfeng; Yang, Ningrui; Ying, Gengning; Zeng, Jun (IEEE transactions on energy conversion, 2024)
A dual-working-modes-based common grounded nonisolated DC-DC converter with a wide voltage-gain range used for photovoltaic applications is proposed in this paper. The proposed converter can flexibly work in dual modes according to external requirements. One working mode is the complementary mode, and the other is the synchronous mode. In complementary mode, the proposed converter can achieve a low or even zero input current ripple, which avoids the use of large electrolytic capacitors at the input side of photovoltaic systems. In synchronous mode, the proposed converter can obtain a wider voltage-gain range to deal with the situation that the input voltage changes sometimes. Besides, common ground can eliminate possible leakage currents between input and output terminals. Analyses of the operating principle and steady-state calculation are presented. Comparisons of the proposed converter under dual working modes with other step-up DC-DC converters show that the proposed converter has higher voltage gain, lower voltage stress, and lower input current ripple with a common grounded characteristic, which is well suited for photovoltaic systems. Finally, a laboratory prototype of 400 V/400 W at 35 kHz switching frequency has been developed to verify the validity and feasibility of the proposed converter.